2002
DOI: 10.1055/s-2002-32421
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime History of Oral Contraceptive Use and Development of Tumours of the Uterus and Ovary*

Abstract: Zusammenfassung Zielstellung: In der Literatur wurde konsistent bei Nutzung oraler Contraceptiva (OCs) ein reduziertes Risiko von Uterus-und Ovarialtumoren berichtet. Der Effekt von niedrigdosierten OCs ist weniger klar. Methodik: Die Deutsche Kohortenstudie zur Frauengesundheit erfasst von Frauen aller Bundesländer, die sich zur Teilnahme bereit erklärt haben, selbst berichtete Daten zur Hormonnutzung. Diese Daten umfassen Angaben zu Zeit, Typ, Dosis der Exposition wie auch zur Zeit des Auftritts von Erkranku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 17 publications
(24 reference statements)
3
12
3
Order By: Relevance
“…We have shown no increased risk for OvC or UC cancers in our own publications, and in fact even weak evidence for a reduced risk in young women using oral contraceptives [4,5].…”
Section: Introductioncontrasting
confidence: 52%
“…We have shown no increased risk for OvC or UC cancers in our own publications, and in fact even weak evidence for a reduced risk in young women using oral contraceptives [4,5].…”
Section: Introductioncontrasting
confidence: 52%
“…The overall risk of breast cancer associated with HRT has shown variation, but has mainly been reported as significantly increased but well under a risk estimate of 2.0 [ 12 , 13 ]. In previous publications, we have shown no increased risk for gynecologic cancers at least – and in fact even weak evidence for preventive properties of sex steroids in young women using oral contraceptives [ 14 - 16 ]. The WHI study results [ 3 ] published in 2002 for breast cancer (BC) and HRT use that showed a significantly increased association with estrogen plus progestin treatment based on combined hormonal therapy of conjugated equine estrogens (CEE) with medroxyprogesterone acetate (MPA).…”
Section: Introductionmentioning
confidence: 75%
“…The study was planned in early 2003 (performed 2004–2005), and was justified by the working hypothesis that the results obtained with the HRT formulation CEE/MPA might be not generalizable for Europe with HRTs of other estrogens and progestins. This study on HRT was made possible by earlier collaborative research with German cancer registries and tumor centers in the field of gynecological cancer and exogenous steroid hormone use [ 14 - 16 ]. The study was designed as a case-control study with lifetime history of exposure and information about patient's characteristics as well as risk factors for BC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an evaluation requires a lifetime history of OC use (calendar method) so that users of old formulations can be distinguished from those who have used only low-dose OCs for long enough to permit an analysis of tumour manifestation, i.e., it depends on how long low-dose formulations are on the market. In a previous publication on the risk of tumours of the uterus and ovary we have shown that the length of availability of low-dose OCs now permits such an evaluation [8].…”
Section: Introductionmentioning
confidence: 99%